Studi Kualitatif: Pengalaman Emosional Ibu yang Mengalami Abortus Spontan - Rabuana, Susi; Rahmat, Rezqiqah Aulia (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Spontaneous abortion is a traumatic experience that not only has physical consequences but also affects the mother's psychological and emotional well-being. Emotional responses, such as sadness, anxiety, anger, and loss of meaning in life, are often overlooked in health care. Objective: This study aims to explore the emotional experiences of mothers who experience spontaneous abortion and understand how they cope with and interpret the event. Methods: This study used a qualitative approach with a phenomenological design. Six mothers who experienced spontaneous abortion within the past year participated. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. Results: Four main themes emerged in this study: (1) a profound sense of loss, (2) feelings of guilt and self-blame, (3) limited emotional support from the surrounding environment, and (4) the process of acceptance and spiritual meaning. The majority of participants indicated a need for psychological support after the event. Conclusion: Spontaneous abortion causes significant emotional distress. Empathy-based interventions and structured psychological support within health care are needed to help mothers cope with the emotional impact after the event.